Accelerator development at the FREIA Laboratory. (21st July 2021) - Ruber, R.; Bhattacharyya, A.K.; Dancila, D.; Ekelöf, T.; Eriksson, J.; Fransson, K.; Gajewski, K.; Goryashko, V.; Hermansson, L.; Jacewicz, M.; Jobs, M.; Jönsson, Å.; et al.
Abstract: The FREIA Laboratory at Uppsala University focuses on superconducting technology and accelerator development. It actively supports the development of the European Spallation Source, CERN, and MAX IV, among others. FREIA has developed test facilities for superconducting accelerator technology such as a double-cavity horizontal test cryostat, a vertical cryostat with a novel magnetic field compensation scheme, and a test stand for short cryomodules. Accelerating cavities have been tested in the horizontal cryostat, crab-cavities cavities in the vertical cryostat, and cryomodules for ESS on the cryomodule test stand. High power radio-frequency amplifier prototypes based on vacuum tube technology were developed for driving spoke cavities. Solid-state amplifiers and power combiners are under development for future projects. We present the status of the FREIA Laboratory complemented with results of recent projects and future prospects.